NEURO-PSYCHOLOGICAL PROFILE OF EPILEPSY ON LURIA-NEBRASKA NEUROPSYCHOLOGICAL BATTERY - Mishra, B.P. (Medknow Publications, 2002)
Neuropsychological functioning of epileptic patients is emerging as an interesting area of research among clinician. There is sufficient evidence suggesting cognitive deficits among epileptics. No specific rehabilitation planning was prepared in this regard. The planning for rehabilitation can be prepared if a comprehensive functional organization of the brain of epileptics can be identified. The present study is directed towards the neuropsychological functioning of patients with idiopathic generalized epilepsies, and its comparison with normal controls. All the 60 subjects (30 normal controls and 30 epileptics), after matching their age and education were assessed on Luria-Nebraska Neuropsychological Battery (LNNB). The performance level and pattern of epileptics were significantly different than normal controls on all the parameters of LNNB. The battery could detect specific organic malfunctioning in epileptic patients.